Development of 2D, 3D-QSAR and Pharmacophore Modeling of Chalcones for the Inhibition of Monoamine Oxidase B - Mathew, Bijo; Herrera-Acevedo, Chonny; Dev, Sanal; Rangarajan, T.M.; Kuruniyan, Mohamed S.; Naseef, Punnoth Poonkuzhi; Scotti, Luciana; Scotti, Marcus Tullius (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Selective and reversible types of MAO-B inhibitors have emerged as promising candidates for the management of neurodegenerative diseases. Several functionalized chalcone derivatives were shown to have potential reversible MAO-B inhibitory activity, which have recently been reported from our laboratory. Methods: With the experimental results of about 70 chalcone derivatives, we further developed a pharmacophore modelling, and 2D and 3D- QSAR analyses of these reported chalcones for MAOB inhibition. Results: The 2D-QSAR model presented four variables (MATS7v, GATS 1i and 3i, and C-006) from 143 Dragon 7 molecular descriptors, with a r2 value of 0.76 and a Q2cv for cross-validation equal to 0.72. An external validation also was performed using 11 chalcones, obtaining a Q2ext value of 0.74. The second 3D-QSAR model using MLR (multiple linear regression) was built starting from 128 Volsurf+ molecular descriptors, being identified as 4 variables (Molecular descriptors): D3, CW1 and LgS11, and L2LGS. Adetermination coefficient (r2) value of 0.76 and a Q2cv for cross-validation equal to 0.72 were obtained for this model. An external validation also was performed using 11 chalcones and a Q2ext value of 0.74 was found. Conclusion: This report exhibited a good correlation and satisfactory agreement between experiment and theory.
Keywords: pharmacophore modeling